A proposed theoretical model to explain relative age effects in sport - Hancock, D. J.; Adler, A. L.; Côté, J. (European Journal of Sport Science, 2013)
Exemplary scientific methods describe concepts and provide theories for further testing. For the field of relative age effects (RAEs) in sport, the scientific method appears to be limited to description. The purpose of this paper is to provide a theoretical model to explain RAEs in sport, which researchers can use to test the effects, as well as to generate new hypotheses and recommendations. Herein, we argue that social agents have the largest influence on RAEs. Specifically, we propose that parents influence RAEs through Matthew effects, coaches influence RAEs through Pygmalion effects and athletes influence RAEs through Galatea effects. Integrating these three theories, we propose a model that explains RAEs through these various social agents. This paper provides a theoretical foundation from which researchers can further understand, explain and eventually use to create policies aimed at limiting the negative effect of relative age in sport.